Synchronization of Catch Fish Data in Fisheries e-Logbook with a Vessel Monitoring System - Abdi Wahab; Bayu Waseso; Hadi Pranoto (Institute for Research on Innovation and Industrial System (IRIS), 2021)
Indonesia as an archipelago country has many residents whose livelihoods is fishermen. Traditional fishermen who are scattered in various provinces need a tool that can help to record fish catch data after they sail. This study aims to propose a method for synchronizing fish catch data between e-logbook and a fishing vessel monitoring system. The Unix timestamp reference was used to help synchronize fish catch data with the position in the monitoring system, and it was expected to run well. The results of this study are fisheries e-logbooks for Android devices equipped with data synchronization features. In the future, it would be better if a tool was made to help transmit data from the middle of the sea for traditional fishermen.